Energy efficiency and Use of renewable energy for residential buildings - code of practice - Sapian, Abdul Razak; Mohamed, Nadiah; Looi, H P; Abdul Majid, Noor Hanita; Denan, Zuraini; Sanusi, Aliyah Nur Zafirah; Lim, Chin How; Zaky Jaafar, Mohamad Fakry; Zain Ahmad, Azni; Zakaria, Zaini Ikrom; Ibrahim, Najib (SIRIM, 2017)
This Malaysian Standard was developed by the Working Group on Architecture and Passive Design Strategy under the authority of the Industry Standards Commitee on Building, Construction and Civil Engineering.